ELPylated avian flu vaccines from plants - Improvement of expression and development of a new purification strategy - Hoang, Phan Trong (Universitäts- und Landesbibliothek Sachsen-Anhalt, 2012)
Hämagglutinin und Neuraminidase des Vogelgrippevirusstammes A/Hatay/2004/(H5N1) wurden in Tabakpflanzen als C-terminale Fusionen mit dem „Elastin-like-Peptide“ (ELP) exprimiert. Dadurch wurden diese Influenzavirusantigene in Pflanzen stärker akumuliert. Membranbasiertes „Inverse Transition Cycling“ wurde genutzt, um ELPylierte Proteine aus Blättern zu reinigen. Diese Methode ist einfach, hocheffizient, skalierbar und erfordert wenig Zeitaufwand. Trimere Hämagglutinine konnten im Gegensatz zu monomeren Hämagglutininen Hühnererythrozyten agglutinieren. Tetramere Neuraminidase zeigte eine neunfach höhere Enzymaktivität als monomere Neuraminidase. ELP beeinflusste die Funktionen der beiden rekombinanten Fusionsproteine nicht. Monomere Hämagglutinine induzierten kaum neutralisierende Antikörper, während trimere Hämagglutinine hohe Titer neutralisierender Antikörper gegen homologe Virus-artige Partikel und gegen heterologe inaktiverte Viren hervorriefen. Hemagglutinin and neuraminidase (monomeric and oligomeric forms) from the highly pathogenic avian influenza A/Hatay/2004/(H5N1) strain were optimally expressed in tobacco plants by fusing with elastin-like polypeptides (ELPs) at the C-terminus. An enhancement of the accumulation of influenza antigens in plants based on ELPylation technology was confirmed. Membrane-based Inverse Transition Cycling (mITC) was developed and applied to successfully purify ELPylated proteins from leaf materials. This method is simple, highly efficient, scalable and less time-consuming. Trimeric hemagglutinins were able to agglutinate chicken erythrocytes, while monomeric hemagglutinins were not able to do so. Similarly, tetrameric neuraminidase exhibited a 9-fold higher enzymatic activity than monomeric neuraminidase. ELP fusion does not affect functionalities of these proteins. Monomeric hemagglutinins induced neutralizing antibodies poorly but trimeric hemagglutinins could induce high neutralizing antibody titers against the homologous virus-like particles and the heterologous ...